The Impact of Hydration and Other Strategies in prevention of Contrast-Induced Nephropathy - Wojtania, Joanna; Łepik, Michał; Uszok, Zofia; Rosiak, Krzysztof; Płeska, Kacper; Reguła, Kacper; Waloch, Kamil; Piaszczyński, Szymon; Czajka, Andrzej; Szymański, Bartłomiej (Quality in Sport, 2024)
Introduction and purpose Contrast-induced nephropathy (CIN) remains a significant concern in clinical practice, particularly among patients undergoing contrast-enhanced imaging or interventional procedures. Characterized by an acute decline in renal function following exposure to contrast media, CIN not only poses substantial morbidity and mortality risks but also presents challenges in patient management and healthcare resource utilization. Despite extensive research efforts, the precise pathophysiology of CIN remains incompletely understood, with multifactorial mechanisms involving renal ischemia, oxidative stress, and direct tubular toxicity implicated in its development. This review explores the impact of hydration and other prophylactic strategies on the prevention of CIN. Numerous studies have demonstrated the effectiveness of various hydration protocols, including isotonic saline and bicarbonate solutions, in reducing the incidence of CIN. Additionally, the review evaluates the efficacy of pharmacological agents such as N-acetylcysteine, statins, and ascorbic acid, as well as emerging techniques like remote ischemic preconditioning.